PREPARATION OF POLYMERIC NANOPARTICLES BY FLOW ULTRASONIC EMULSIFICATION - Yu. M. Domnina; S. A. Kedik; V. V. Suslov; E. A. Shnyak; S. S. Kryukova (Тонкие химические технологии)
The work is dedicated to the production of polymer suspensions using ultrasonic dispergation in a flow mode. An apparatus was designed on the basis of a Russian flow ultrasonicator. The applicability of this apparatus for obtaining aqueous dispersions of polymeric micro- and nanoparticles by means of one-step emulsification followed by solvent extraction / evaporation was demonstrated. The influence of the process parameters on the characteristics of the obtained suspensions was studied. The particle size distribution and the average size of the resulting particles were evaluated by using Delsa Nano S, Beckman Coulter laser analyzer (USA). The dependence of the average diameter of the suspension particles on the stabilizer concentration and on the change of the phases feed rate was shown. When polyvinyl alcohol was used as a stabilizer in the concentration range 0.5-2%, the average particle size was 30-400 nm. The feed rates of the aqueous and organic phases affect the nature of the particle size distribution.